2000
DOI: 10.1109/81.847870
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations in two-dimensional piecewise smooth maps-theory and applications in switching circuits

Abstract: The dynamics of a number of switching circuits can be represented by one-dimensional (1-D) piecewise smooth maps under discrete modeling. In this paper we develop the bifurcation theory of such maps and demonstrate the application of the theory in explaining the observed bifurcations in two power electronic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(112 citation statements)
references
References 29 publications
5
106
0
1
Order By: Relevance
“…23,25 By contrast, we consider a situation where an attracting fixed point changes into a spirally repelling fixed point as it moves across the border.…”
Section: The Piecewise Linear Normal Formmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 By contrast, we consider a situation where an attracting fixed point changes into a spirally repelling fixed point as it moves across the border.…”
Section: The Piecewise Linear Normal Formmentioning
confidence: 99%
“…Among other phenomena, Nusse and Yorke emphasized the possibility of observing peculiar bifurcations such as direct transitions from period-2 to period-3 dynamics or from regular periodic motion into chaos. Banerjee et al [23][24][25] developed the theory of border-collision bifurcations in oneand two-dimensional piecewise smooth maps, and illustrated its application in power electronic systems. It was shown that the so-called corner-collision, sliding and grazing bifurcations all belong to this class.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11͑a͒ shows the phase portrait after the perioddoubling bifurcation. The phase portrait contains the points of the unstable cycles with the periods 4,8,12,16,24,32, and 40. As mentioned above, these cycles arise through a border-collision bifurcation occurring at the same parameter value as the period doubling, L = L * .…”
Section: B Period-doubling Border-collision Routementioning
confidence: 99%
“…From Appendix A, we have the explicit expression of all the stable k-cycles, which the map f(X n ) can have, and from the first equation in Eqs. (22), via the reverse function…”
Section: B Stable K-cycles and Chaosmentioning
confidence: 99%